Prevalence of chromosomal aberrations in Argentinean agricultural workers - Bianco, Graciela Eugenia; Suarez, Eva; Cazon, Lauro; de la Puente, Teresita Beatriz; Ahrendts, Marcelo Rafael Benitez; De Luca, Julio César (Environmental science and pollution research international, 2017)
Little is known about biosecurity measures and toxic effects during pesticide application in the province of Jujuy, Argentina, particularly concerning the protective measures and mixture of pesticides used by rural workers. We carried out an observational study of agricultural workers from Jujuy (76 exposed subjects and 53 controls) to investigate the prevalence of chromosomal aberrations (CAs) in human lymphocytes as well as the activity level of acetylcholinesterase (AChE) in red blood cell erythrocytes. Whole blood samples (5 mL) were collected in heparinized Vacutainer tubes for cytogenetic analysis and erythrocyte cholinesterase activity determination according to Ellman’s method. Cytogenetic results showed a significant CA increase in pesticide-exposed individuals as compared with controls (4.20 ± 0.15 vs. 1.00 ± 0.05, respectively; p < 0.001), suggesting that pesticides are clastogenic agents causing DNA damage. Erythrocyte cholinesterase activity was significantly lower in exposed individuals, evidencing the possible occurrence of perturbations in blood as well as neurotoxicity in pesticide sprayers. These results suggest the need for periodic biomonitoring of these biomarkers together with education and training of occupational workers for the safe application of potentially harmful pesticides.